Avaliação do uso da terapia dirigida por metas na reversão da injúria renal aguda em pacientes internados em unidade de terapia intensiva - Amendola, Cristina Prata (2017)
Introduction: Acute kidney injury (AKI) is observed in a substantial proportion of patients admitted to intensive care unit and is a significant predictor of poor outcomes. The management of hemodynamic and oxygenation parameters, known as goal-directed therapy (GDT), may prevent AKI, however, it is not known if this treatment strategy can mitigate renal impairment or decrease mortality in patients with early AKI. Background: To assess whether GDT promoted in the early stage of AKI can change AKI course. Material and Methods: This was a prospective, randomized, controlled, and multicenter study carried out in the Intensive Care Unit. Patients with early AKI were randomly allocated to a standard care (Control) or GDT group with 8-h intensive treatment to maximize oxygen delivery. The two groups were monitored until hospital discharge or death. Results: A total of 143 patients were eligible and 99 patients were randomized either of the two groups. In the GDT group, central venous oxygen saturation (ScvO2) significantly increased and serum lactate significantly declined (p = 0.001) compared with the Control group (p = 0.572). A lactate clearance higher or equal 10% during GDT was associated with a significant decrease in the odds of death (OR 0.37 IC 95% 0.14-0.97, p=0.044). There was no difference in SCr difference (p=0.96) or the need for renal replacement therapy between groups (p = 0.82). In-hospital mortality was significantly decreased in the GDT group (33% vs. 51%; RR: 0.61, CI 95% 0.37−1.00, p = 0.048, Number needed to treat = 5). Conclusion: GDT in patients with early AKI did not change AKI course but it seems to determine better survival.